Images of cosmology in Jewish and Byzantine art : God's blueprint of creation - Laderman, Shulamith. (Jewish and Christian Perspectives Series, 2013)
Does the design of the Tabernacle in the wilderness correspond to God's blueprint of Creation? The Christian Topography, a sixth-century Byzantine Christian work, presents such a cosmology. Its theory is based on the "pattern" revealed to Moses on Mount Sinai when he was told to build the Tabernacle and its implements "after their pattern, which is being shown thee on the Mount." (Exod. 25: 40). The book demonstrates, through texts and images, the motifs that link the Tabernacle and Creation. It traces the long chain of transmission that connects the Jewish and Christian traditions from Syria and ancient Israel to France and Spain from the first through the fourteenth century, revealing new models of interaction between Judaism and Christianity.